Application of Ex Vivo Normothermic Machine Perfusion in Deceased Donors With Acute Kidney Injury With Successful Renal Transplantation: A Preliminary Experience. Issue 11 (24th October 2022) - Choudhary, Devprakash; Sharma, Ashish; Singh, Sarbpreet; Kenwar, Deepesh B.; Walker Minz, Ranjana; Singh Kohli, Harbir; Nada, Ritambhra; Wangkheimayum, Sujata; Jain, Kajal; Patil, Shivakumar S.
Abstract : Background: Ex vivo normothermic machine perfusion (NMP) has improved organ preservation and viability assessment among heart, liver, and lung transplantation. However, literature regarding the application of NMP in human clinical kidney transplantation remains limited. Numerous kidneys, especially from donors with stage 3 acute kidney injury (AKI), are not utilized concerning the high rate of delayed graft function (DGF) and primary nonfunction. The present study investigated the impact of NMP (135–150 min) on short-term outcomes after kidney transplantation from deceased donors with AKI. Methods: Graft outcomes of NMP kidneys were compared with contralateral kidneys stored in static cold storage (SCS) from the same donor with AKI during December 2019–June 2021. The study's primary aim is to assess the safety and feasibility of NMP in deceased donors with AKI. The primary outcome was DGF. Secondary outcomes were duration of DGF, biopsy-proven rejection, postoperative intrarenal resistive index, postoperative infections, hospital stay duration, primary nonfunction, and kidney function estimated glomerular filtrate rate at discharge, 3 mo, and 1 y. Results: Five pairs of AKI kidneys (NMP versus SCS) were included in the final analysis. The results show no statistically significant differences in clinical outcomes between NMP versus SCS kidneys; however, NMP kidneys demonstrated slightly improved estimated glomerular filtrate rate at 3 mo (59.8 ± 5.93 [59] versus 75.20 ± 14.94 [74]) mL/min/1.73 m 2 ( P < 0.065) and at the last follow-up (12–29 mo) (72.80 ± 10.71 [75]) versus (94 ± 22.67 [82]) mL/min/1.73 m 2 ( P < 0.059) as compared with SCS kidneys. A higher proportion of NMP kidneys had normal intrarenal resistive index (0.5–0.7) and mild acute tubular injury on protocol biopsy, suggesting NMP is safe and feasible in deceased donors with acute kidney injury. Conclusions: NMPs of AKI donor kidneys are safe and feasible. A larger cohort is required to explore the reconditioning effect of NMP on AKI kidneys. Abstract :